Half the story: Thermal effects on within‐host infectious disease progression in a warming climate. (1st September 2017) - Stewart, Alexander; Hablützel, Pascal I.; Brown, Martha; Watson, Hayley V.; Parker‐Norman, Sophie; Tober, Anya V.; Thomason, Anna G.; Friberg, Ida M.; Cable, Joanne; Jackson, Joseph A.
Abstract: Immune defense is temperature dependent in cold‐blooded vertebrates (CBVs) and thus directly impacted by global warming. We examined whether immunity and within‐host infectious disease progression are altered in CBVs under realistic climate warming in a seasonal mid‐latitude setting. Going further, we also examined how large thermal effects are in relation to the effects of other environmental variation in such a setting (critical to our ability to project infectious disease dynamics from thermal relationships alone). We employed the three‐spined stickleback and three ecologically relevant parasite infections as a "wild" model. To generate a realistic climatic warming scenario we used naturalistic outdoors mesocosms with precise temperature control. We also conducted laboratory experiments to estimate thermal effects on immunity and within‐host infectious disease progression under controlled conditions. As experimental readouts we measured disease progression for the parasites and expression in 14 immune‐associated genes (providing insight into immunophenotypic responses). Our mesocosm experiment demonstrated significant perturbation due to modest warming (+2°C), altering the magnitude and phenology of disease. Our laboratory experiments demonstrated substantial thermal effects. Prevailing thermal effects were more important than lagged thermal effects and disease progression increased or decreased in severity with increasing temperature in an infection‐specific way. Combining laboratory‐determined thermal effects with our mesocosm data, we used inverse modeling to partition seasonal variation in Saprolegnia disease progression into a thermal effect and a latent immunocompetence effect (driven by nonthermal environmental variation and correlating with immune gene expression). The immunocompetence effect was large, accounting for at least as much variation in Saprolegnia disease as the thermal effect. This suggests that managers of CBV populations in variable environments may not be able to reliably project infectious disease risk from thermal data alone. Nevertheless, such projections would be improved by primarily considering prevailing thermal effects in the case of within‐host disease and by incorporating validated measures of immunocompetence. Abstract : We demonstrate that immunity and infectious disease progression in cold‐blooded vertebrates are perturbed when a realistic climate warming scenario is superimposed upon mid‐latitude environmental cycles: altering the magnitude and phenology of disease. Importantly, we partition seasonal thermal effects on disease progression from effects due to other natural temporal environmental variation and show that the latter may be relatively large. Hence, warming effects on infectious disease dynamics in nature will be more complex to predict than is generally appreciated.